2016
DOI: 10.29252/arakmu.10.3.47
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ELISA and TLC Methods for the Morphine Detection in Urine of Drug Abusers

Abstract: Background:The current study was conducted to compare ELISA with thin layer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The previously mentioned drugs could result in drug interaction mainly in the rapid strip tests and to less extent in EMIT leading to false positive or false negative results when compared with the TLC technique. This has coincided with Timcheh-Hariri et al (13) who reported higher specificity of the TLC technique in detecting false-positive results by immunoassays.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The previously mentioned drugs could result in drug interaction mainly in the rapid strip tests and to less extent in EMIT leading to false positive or false negative results when compared with the TLC technique. This has coincided with Timcheh-Hariri et al (13) who reported higher specificity of the TLC technique in detecting false-positive results by immunoassays.…”
Section: Discussionsupporting
confidence: 78%
“…According to manufacturers' claims, no crossreactivity was found for many non-related medications to morphine derivatives at different concentrations in urine. Still, related compounds to morphine had been analyzed by the qualitative method and cross-reactivity could exist (13) .…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, it was also concluded that although TLC is more specific, it is more time-consuming and less-sensitive, in comparison to ELISA. It is worth mentioning that although TLC is an old method, it is much more reliable than ELISA (10).…”
Section: Discussionmentioning
confidence: 99%